Pembelajaran Matematika Berbantuan Game Bagi Anak-Anak KBG Santa Ursula - Alberta Parinters Makur; Maria Graseliani Medot; Priska W. P. Ruslan; Rosantri Ermelinda; Maria A. L. Belos; Yohanes J. Siga (Randang Tana - Jurnal Pengabdian Masyarakat, 2022)
The prolonged Covid-19 pandemic has an impact on the learning process in schools which must be abolished and replaced by learning from home. Learning from home, especially mathematics, reduces students' enthusiasm for learning and grows a sense of laziness in learning among students because they prefer to play rather than study. This also happened to students in the Santa Ursula KBG environment. With such conditions, the author uses the media of math games to help children at KBG Santa Ursula in learning mathematics. The results of the activities that have been carried out show that the use of math games increases the enthusiasm for learning and reduces the laziness of the children at the Santa Ursula KBG in learning mathematics